Re‐animation: multimodal discourse around text. (16th November 2021) - Bryer, Theodora; Coles, Jane
Abstract: This article offers a multimodal analysis of spontaneous, improvisatory interactions between pre‐service teachers as they engage with a range of material resources connected to, or generated by, a literary text (in this case, the Old English poem Beowulf ). We draw on an understanding of role as a form of frame, offering students a particular perspective on the material that they engage with and a heightened awareness of the signs that they make, and we consider the function of role in supporting learning. Using video evidence collected across a 2‐day workshop, we select two key episodes for close analysis to illustrate the complex ways in which learners' spoken words, gestures and bodies combine in the processes of shared meaning‐making, aspects of learning that tend to be ignored in official accounts of classroom literacy. In particular, we identify fleeting yet generative moments of role play that learners adopt while engaged in collaborative activities around images and a touchscreen, a form of embodied response we term 're‐animation'.